Integrating Internet of Things, Provenance, and Blockchain to Enhance Trust in Last Mile Food Deliveries - Markovic, Milan; Jacobs, Naomi; Dryja, Konrad; Edwards, Peter; Strachan, Norval J. C. (Frontiers in Sustainable Food Systems, 2020)
In this article, we discuss our experience of realising a prototype IoT-based food safety monitoring solution which integrates inexpensive off-the-shelf open source IoT technology for monitoring food deliveries, semantic services for managing and reasoning about food safety provenance records, and private blockchain networks for persistent and secure storage of semantic provenance graphs. We describe how observation of real-world contexts was used to develop a prototype device, and the results of field trials deploying these prototypes as part of the food delivery process. Results indicate that continuous, context sensitive, trustworthy temperature measurement could provide benefits to multiple stakeholders across the delivery pathway. However, close attention has to be paid to the technology used - as cheap multi-functional IoT devices may produce low quality sensor observations which adversely affect the utility of the overall solution. Our experience also suggests that future food safety management systems may need to include machine-processable guidelines to support analysis of raw sensor data for food safety compliance.